The Dialogue of Civilizations in the Birth of Modern Science - Bala, A. author. aut Link
XII, 230 p.
Keywords: Arun Bala challenges Eurocentric conceptions of history by showing how Chinese, Indian, Arabic, and ancient Egyptian ideas in philosophy, mathematics, cosmology and physics played an indispensable role in making possible the birth of modern science.